Numerical study on the heat preservation of the ladle used for twin-roll strip casting. (May 2015) - Dong, J. H.; Chen, M.; Wang, N.
<x content-type="archive" xml:space="preserve">Abstract</x> To adapt to the requirements of temperature variations in the process of twin-roll strip casting, a three-dimensional mathematical model was developed to analyze the heat transfer and temperature drop in the ladle using the finite volume method in the present study. The results showed that the temperature drop rate of the melt was 1·1 K·min−1 in the ladle of traditional casting, which could not satisfy with the demands in the process of twin-roll strip casting, and the temperature drop rate of the melt was 0·31 K·min−1 when more than 40 mm of a shielding agent was added on the slag surface and nanoporous materials were used as an insulation layer with thickness of more than 16 mm, which is considered to be favourable to provide the suitable temperature drop of the melt in the ladle to maintain the twin-roll strip casting process and improve the strip quality.